PERENCANAAN FASHION CENTER DIKOTA SAMARINDA - Prabowo, Taufik Sigit; Milasari, Lisa Astria; Huda, Khoirul (Jurnal Totem : Architecture, Environment, Region and Local Wisdom, 2021)
Fashion Show activities in the city of Samarinda are quite often held, both single events and filler events. The development of clothing in the city of samarinda is currently still developing with the fashion show event that is often held in the city of samarinda as well as the existence of a vocational school in the field of Clothing and Fashion Agency. How to plan a Fashion Center with the concept of Eco-Tech Architecture focus on the principles of the Civic Symbolic. The purpose of this research is to create a Fashion Center in the city of samarinda to support the interests and talents of the people in the field of Fashion with the concept of Eco-Tech architecture focusing on the principles of Civic Symbolis. The method used to achieve goals and objectives consists of primary data and secondary data. The results of the discussion in this study are that the Fashion Center planning using Eco-Tech architectural concepts is focused on the Civic Symbolic principle by adopting a form of dayak shield which is emphasized on the building facade as a point entrance. Analysis of the size of the room with a total area of mÂ², KDH, KDB, with a total of 26 rooms, for the main hall of the exhibition hall and modeling classrooms, site analysis was selected on Jalan M. Yamin, Kelurahan Gunung Kelua. The concept of composition uses axial, the concept of landscape uses formations from fashion.Â Keyword : Planning, Fashion Center, Eco-Tech